The Implementation Guided Inquiry Learning and Students' Science Process Skills on the Topic of pH Trajectory Determination of Natural Acid-Base Indicators - Aldi Kusuma; Intan Aulia Rahmadani; Laksmi Rahmaning; Sukemi Sukemi; M. Amir Masruhim; Yuli Hartati; Wirhanuddin Wirhanuddin (FKIP - Universitas Riau, 2026)
Science process skills (SPS) are the students’ foundation for thinking scientifically, systematically, and critically to achieve a deep understanding of science concepts. This study aimed to analyze the implementation of guided inquiry learning and students’ SPS in determining the pH trajectory of natural acid–base indicators. A one-shot case study design was used involving 98 eleventh-grade students divided into three learning groups at a public senior high school in Samarinda. Learning implementation was measured through observation, while students’ SPS was assessed using tests, observations, and document analysis. Data were analyzed descriptively and inferentially using the Kolmogorov–Smirnov test for normality and the Kruskal–Wallis test for group differences. The results showed that teacher and student activities were in the excellent category (100% and 86–98%, respectively). The average SPS scores were in the fair category (69.31±5.20, 70.40±6.67, and 72.91±6.06). The Kruskal–Wallis test (p=0.082) indicated no significant difference among groups. Basic and procedural skills, i.e, observing, using tools and materials, and conducting experiments, developed very well, while higher-order thinking skills, i.e., interpreting, communicating, and formulating hypotheses, remained relatively low. Guided inquiry supports basic skills but requires reinforcement to improve higher-order scientific thinking skills.